Perspectives on the Self : Reflexivity in the Humanities. - Kolman, Vojtěch; Matějčková, Tereza (Berlin/Boston : Walter de Gruyter GmbH, 2022)
The series publishes monographs and essay collections devoted to the history of philosophy as well as studies in the theory of writing the history of philosophy. A special emphasis is placed on the contextualization of philosophical historiography into the areas of the history of science, culture, and the wider scope of intellectual history.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books